INFLUENCE OF STELL PLATE SURFACE ROUGHNESS ON COAL FREEZING ADHESIVE STRENGTH - WANG ChunHua; QU Hui; XU HanWen; WANG ZhongXian (Jixie qiangdu)
The coal is the basic raw material for energy in China. It has strategic role in national economy,while the problems of roller surface adhesion,belt jitter,falling coal along return trip caused by coal freezing adhesion seriously restrict coal transportation in winter. Prior studies show that surface roughness has an important effect on freezing adhesion,in order to alleviate the freezing adhesive problems of coal by improving the material’s surface shape,our research group designed the freezing adhesive strength test device,under the certain frozen condition,freezing adhesive characteristics of six different roughness steel plates with moisture content 40% of the coal slime were tested. The results show that,the coal freezing adhesive strength with the change of roughness in W curve,appears minimum value when Ra= 9 10 μm,further suggest that appropriate surface roughness can reduce coal freezing adhesive strength. Thesis has guiding significance on mechanism research of freezing adhesion and other anti-freezing adhesive engineering fields.